Colorandes UTC - Chadan Analuiza, Edwin Aníbal (2016)
The research project titled as "COLORANDES UTC" was focused on the extraction of pear fruit colorant (Opuntia ficus-indica (L) Miller) considering that the fruit owns betanin which gives the food characteristics. It was used the extraction method of soxhlet, in a boiled temperature, for the natural pigment extraction it was used ethyl alcohol to 96º, the alcohol at 96º was blended with the prickly-pear fruit juice and it began the repose of 12 hours with no sun light that helps the alcohol absorbs the prickly-pear fruit pigment. The solids of the solution were sieved with the help of a canvas. Finally, the solution was put in the soxhlet machine where a last strain was made giving 2 Kg of natural colorant as a result 1000 ml. Consequently, the natural colorant was out into physical and chemical analysis (wet and total of solids) and into a microbiological analysis (mesophilic, aerobic, total coliforms, Escherichia coli, molds and yeast).